DNA Barcoding of Fish, Insects, and Shellfish in Korea - Dae-Won Kim; Won Gi Yoo; Hyun Chul Park; Hye Sook Yoo; Dong Won Kang; Seon Deok Jin; Hong Ki Min; Woon Kee Paek; Jeongheui Lim (Genomics & Informatics)
DNA barcoding has been widely used in species identification and biodiversity research. A short fragment of the mitochondrial cytochrome c oxidase subunit I (COI) sequence serves as a DNA bio-barcode. We collected DNA barcodes, based on COI sequences from 156 species (529 sequences) of fish, insects, and shellfish. We present results on phylogenetic relationships to assess biodiversity the in the Korean peninsula. Average GC% contents of the 68 fish species (46.9%), the 59 shellfish species (38.0%), and the 29 insect species (33.2%) are reported. Using the Kimura 2 parameter in all possible pairwise comparisons, the average interspecific distances were compared with the average intraspecific distances in fish (3.22 vs. 0.41), insects (2.06 vs. 0.25), and shellfish (3.58 vs. 0.14). Our results confirm that distance-based DNA barcoding provides sufficient information to identify and delineate fish, insect, and shellfish species by means of all possible pairwise comparisons. These results also confirm that the development of an effective molecular barcode identification system is possible. All DNA barcode sequences collected from our study will be useful for the interpretation of species-level identification and community-level patterns in fish, insects, and shellfish in Korea, although at the species level, the rate of correct identification in a diversified environment might be low.